A cadaveric study on the variations of the profunda femoris artery in South India - George, Anne; Santhakumary, Maheswary Thampi (Asian Journal of Medical Sciences, 2021)
Background: The knowledge of the variations in the branching patterns of the arteries in the femoral triangle is important to avoid iatrogenic injury to the vessels during clinical procedures. Aims and Objectives: The study was designed to explore the varying positions of the origin of the profunda femoris artery from the femoral artery. Materials and Methods: We have dissected the thighs of 60 embalmed bodies. The midpoint between the anterior superior iliac spine and the pubic symphysis was marked (midinguinal point). The distance of the point of origin of profunda femoris artery (PFA) from the femoral artery (FA) to the midinguinal point (MIP) was measured by black silk thread and scale. The relation of PFA to FA at its origin was noted. Results: In the majority of the cases, the PFA was found to arise posterolaterally from the FA. In 63.3% of the cases, PFA was found to arise posterolaterally from the FA, while in 21.5% of cases it took origin laterally from it. In majority of the cases, the PFA arose at a distance of 3-6 cms from midinguinal point while a considerable number originated more distally. Conclusion: PFA exhibits significant variations. Posterolateral origin from FA was the most common mode of origin.